Tollyjoy: Growing with baby steps - Singapore Management University (Institutional Knowledge at Singapore Management University, 2018)
CEO Tan Wee Keng was thrust reluctantly onto the hot seat following his father’s untimely demise. He has since grown the company and is planning for succession